Transient receptor potential vanilloid subtype 1: A potential therapeutic target for fibrotic diseases - Peng, Guangxin; Tang, Xiaoling; Gui, Yang; Yang, Jing; Ye, Lifang; Wu, Liuyang; Ding, Ya hui; Wang, Lihong (Frontiers in Physiology, 2022)
The transient receptor potential vanilloid subtype 1 (TRPV1), belonging to the TRPV channel family, is a non-selective, calcium-dependent, cation channel implicated in several pathophysiological processes. Collagen, an extracellular matrix component, can accumulate under pathological conditions and may lead to the destruction of tissue structure, organ dysfunction, and organ failure. Increasing evidence indicates that TRPV1 plays a role in the development and occurrence of fibrotic diseases, including myocardial, renal, pancreatic, and corneal fibrosis. However, the mechanism by which TRPV1 regulates fibrosis remains unclear. This review highlights the comprehensive role played by TRPV1 in regulating pro-fibrotic processes, the potential of TRPV1 as a therapeutic target in fibrotic diseases, as well as the different signaling pathways associated with TRPV1 and fibrosis.